DETERMINATION OF THE ANTIOXIDANT ACTIVITY OF WILLOW COMPOUNDS (Scientific journal of the Fergana State University, 2025)
This article presents the results of a study of the antioxidant activity of mixtures prepared from willow plants growing in the Fergana Valley. The antioxidant activity of various mixtures prepared from these plants was studied spectrometrically. The antioxidant activity was analyzed at different time intervals, comparing it with adrenaline and vitamin C taken as standards. The results showed that the mixture prepared from willow roots and willow stems (1:1) exhibited higher antioxidant properties than vitamin C.